2005
DOI: 10.1038/sj.npp.1300944
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogen-Induced UP States in the Brain Slice of Rat Prefrontal Cortex: Role of Glutamate Spillover and NR2B-NMDA Receptors

Abstract: Psychedelic hallucinogens (eg LSD or DOI) induce disturbances of mood, perception, and cognition through stimulation of serotonin 5-HT 2A receptors. While these drugs are not proconvulsant, they have been shown by microdialysis to increase extracellular glutamate in the prefrontal cortex. Electrophysiological studies in the rat prefrontal slice have shown that both LSD and DOI enhance a prolonged, late wave of glutamate release onto layer V pyramidal neurons after an electrical stimulus. Here, we hypothesize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 57 publications
(82 reference statements)
2
44
0
2
Order By: Relevance
“…Studies by Lambe and Aghajanian (2006) further examined the basis for the enhanced late wave of extrasynaptic transmission of glutamate in PFC brain slices of the rat. They retarded the diffusion of glutamate beyond the synapse by increasing the viscosity of the extracellular space using a solution of dextran, a procedure known to suppress glutamate spillover.…”
Section: Role Of Glutamatementioning
confidence: 99%
“…Studies by Lambe and Aghajanian (2006) further examined the basis for the enhanced late wave of extrasynaptic transmission of glutamate in PFC brain slices of the rat. They retarded the diffusion of glutamate beyond the synapse by increasing the viscosity of the extracellular space using a solution of dextran, a procedure known to suppress glutamate spillover.…”
Section: Role Of Glutamatementioning
confidence: 99%
“…The most prominent effect elicited by the activation of these receptors is an increase of both spontaneous glutamate-mediated synaptic activity and pharmacologically induced NMDA currents (20,50,51). It has been hypothesized that they result from an increase in glutamate release from thalamocortical fibers elicited by either activation of presynaptic 5-HT 2A receptors expressed on thalamocortical axons/terminals or a putative retrograde messenger produced by pyramidal neurons upon activation of postsynaptic receptors (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we propose that a higher quantity of NR2B subunits is important for online processing of PFC functions, as previous modeling predicted (10), because only the slow-decayed NR2B expression could allow greater temporal integration of asynchronous synaptic inputs (33) and cross talk among multiple synapses (30) than those with NR2A subunits. Indeed, a recent study reported that NMDAR channels with a higher proportion of NR2B subunits are critical for network activity in the prefrontal circuitry because hallucinogen-induced upstate in the PFC could be blocked by application of NR2B antagonist (37).…”
Section: Discussionmentioning
confidence: 99%